2016
DOI: 10.1016/j.jcat.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure vapor-phase hydrodeoxygenation of lignin-derived oxygenates to hydrocarbons by a PtMo bimetallic catalyst: Product selectivity, reaction pathway, and structural characterization

Abstract: High-pressure, vapor-phase, hydrodeoxygenation (HDO) reactions of dihydroeugenol (2methoxy-4-propylphenol), as well as other phenolic, lignin-derived compounds, were investigated over a bimetallic platinum and molybdenum catalyst supported on multi-walled carbon nanotubes (5%Pt2.5%Mo/MWCNT). Hydrocarbons were obtained in 100% yield from dihydroeugenol, including 98% yield of the hydrocarbon propylcyclohexane. The final hydrocarbon distribution was shown to be a strong function of hydrogen partial pressure. Kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 55 publications
2
20
0
Order By: Relevance
“…Experimental results and DFT calculation indicated that Mo sites on the surface of PtMo significantly lower the energy barrier for m ‐cresol tautomerization and subsequent deoxygenation process, resulting the introduction of tautomerization‐deoxygenation pathway for PtMo catalyst in contrast to the ring hydrogenation pathway over Pt catalyst . PtMo/MWCNT catalyst employed in HDO of dihydroeugenol, a more complicate lignin‐derived monomers, showed high activity, with unprecedented high yield of hydrocarbon propylcyclohexane (yield≈98 %) . The reaction pathways in PtMo/MWCNT catalytic system is presented in Figure .…”
Section: Hydrodeoxygenation Using H2mentioning
confidence: 99%
“…Experimental results and DFT calculation indicated that Mo sites on the surface of PtMo significantly lower the energy barrier for m ‐cresol tautomerization and subsequent deoxygenation process, resulting the introduction of tautomerization‐deoxygenation pathway for PtMo catalyst in contrast to the ring hydrogenation pathway over Pt catalyst . PtMo/MWCNT catalyst employed in HDO of dihydroeugenol, a more complicate lignin‐derived monomers, showed high activity, with unprecedented high yield of hydrocarbon propylcyclohexane (yield≈98 %) . The reaction pathways in PtMo/MWCNT catalytic system is presented in Figure .…”
Section: Hydrodeoxygenation Using H2mentioning
confidence: 99%
“…While different catalysts including metals [2][3][4][5][6][7][8][9][10][11], metal sulfides [12][13][14], metal phosphides [15][16][17][18][19] and metal carbides [20][21][22] have been investigated in the HDO process, the supported metal catalysts such as Pt, Pd, Ru and Fe have been shown to be promising for the hydrodeoxygenation reactions of phenolic compounds [2][3][4][5][6][7][8][9][10]. Various aspects of the metal catalysts such as the incorporation of bifunctionality [23][24][25][26][27][28][29][30][31], use of bimetallics, [32][33][34][35][36][37][38] and metal-support effects [39][4...…”
Section: Introductionmentioning
confidence: 99%
“…Noble metals such as Pt [175,196,201,271,[276][277][278][279][280][281][282], Pd [185,196,206,274,275,281,[283][284][285][286], and…”
Section: Noble Metalsmentioning
confidence: 99%